Body Mass Index Profile and Men Athlete Canoeing Performance Number 1000 meter - Syahid Nur Yasin; Amung Ma'mun; Agus Rusdiana; Ade Gafar Abdullah; Lutfi Nur (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2020)
This study was aimed at determining the profile of body mass index (BMI) and performance of men athlete Canoeing Number 1000 Meter. This research is a descriptive study involving 19 athletes in the national training camp, for the preparation of the 2018 Asian Games, as the samples. The instrument used were an anthropometric test and a performance test for a 1000 meter canoeing athlete with a canoeing ergometer. Data were analysed by using descriptive statistical techniques. The results showed that the average BMI of the athletes was in the ideal category and the athlete's performance was in the moderate category. The results of this study are expected to be a reflection for both the coaches and the athletes as an effort to improve performance to meet the expected targets. AbstrakPenelitian ini bertujuan untuk mengetahui profil indeks massa tubuh (IMT) dan Performa Atlet Putra Nomor Canoeing 1000 Meter. Penelitian ini merupakan penelitian Deskriptif dengan jumlah sampel sebanyak 19 atlet pada pemusatan latihan nasional untuk persiapan Asian Games 2018. Instrumen yang digunakan adalah tes antropometri dan tes performa atlet nomor Canoeing 1000 meter dengan ergometer canoeing. Data dianalisis dengan menggunakan teknik statistik deskriptif. Hasil penelitian menunjukkan bahwa rata-rata IMT atlet berada pada kategori ideal dan performa atlet berada pada kategori cukup. Dari hasil penelitian ini diharapkan dapat menjadi refleksi baik bagi pelatih maupun atlet sendiri dalam upaya meningkatkan performa sesuai dengan target yang diharapkan.